Determination of optimum sowing date for higher productivity and profitability in sesamum (Sesamum Indicum L) - Sujatha, V; Saritha , R; Sirisha, ABM (Bangladesh Journal of Botany, 2023)
In the context of optimizing sowing dates for realizing higher productivity and profitability for sesamum an experiment with twelve different sowing dates (T1 to T12) from second fortnight of December to first fortnight of June at 15 days interval was executed at Agricultural Research Station, Yellamanchili, Andhra Pradesh, India during rabi-summer and kharif, 2015-16 and 2016-17. The findings revealed that during rabi –summer, sesamum sown on second and first fortnight of January (T3 and T2) recorded highest seed yield (541.1 and 509.3 kg/ha), oil content (46.33 and 46.20 %), net returns (Rs.29878 ha-1and Rs. 27330 ha-1) and BC ratio (2.23 and 2.04) and during kharif, sowing on second fortnight of May and first fortnight of June (T11 and T12) produced significantly higher seed yield (323.7 and 258.4 kg ha-1), oil content (45.98 and 45.88 %),net returns (Rs.14886 ha-1and Rs.9658 ha-1) and BC ratio (1.36 and 0.88) than rest of sowing dates. Delay in sowing after first fortnight of February gradually decreased the seed yield of sesamum. Significantly the lowest seed yield (70.4 and 87.0 kg ha-1, respectively) and negative net returns were obtained when crop was sown on first and second fortnight of April (T8 and T9). Bangladesh J. Bot. 52(3): 883-887, 2023 (September)